Detection of an A-factor-responsive protein that binds to the upstream activation sequence of strR, a regulatory gene for streptomycin biosynthesis in Streptomyces griseus. - Vujaklija, D (1993)
DNA-binding assays using mobility shift polyacrylamide gel electrophoresis revealed the presence of a protein that specifically bound to a restriction fragment -288 to -191 bp upstream from the transcriptional start point of strR, a regulatory gene for streptomycin biosynthesis in Streptomyces griseus. The binding site corresponded to an upstream activation sequence predicted from the results of in vivo promoter assays. The binding was greatly enhanced by 5 mM Mg2+. This binding was detected with the protein source only from the wild-type strain and not from an A-factor-deficient mutant strain. The exogenous supplementation of A-factor to the A-factor-deficient mutant strain caused the appearance of the protein in the DNA-binding assay. A synthetic nucleotide 52 bp in length (region from -293 to -242), which was synthesized on the basis of data obtained from both retardation assays with dissected DNA fragments and in vivo promoter assays, was retarded by the A-factor-dependent protein. In addition to this A-factor-dependent protein, at least three proteins with different recognition site affinities capable of binding to the upstream region of the strR promoter were detected. The binding of one of these proteins to both sides of the upstream activation sequence bound by the A-factor-dependent protein was completely abolished in the presence of ATP and Mg2+ in the incubation mixture. The region bound by these proteins showed anomalous electrophoretic mobility, like that of a bent DNA molecule, which is probably caused by the presence of many blocks consisting of A and T. The region bound by these proteins was found to be transcribed in the orientation opposite to that of strR.